2015
DOI: 10.1115/1.4031298
|View full text |Cite
|
Sign up to set email alerts
|

On the Geometric Accuracy of RepRap Open-Source Three-Dimensional Printer

Abstract: In the field of additive manufacturing (AM) processes, there is a significant lack of scientific data on the performance of open-source 3D printers in relation to process parameter values. The purpose of this paper is to assess the impact of the main process parameters on the accuracy of a set of typical geometric features, as obtained with an open-source 3D printer, the RepRap Prusa-Mendel I2. For this purpose, a benchmarking part was set up, composed of elementary shapes, representing a series of different g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The accuracy of the part to its digital counterpart has been analysed by Sood et al [12] who applied Taguchi's design of experiments on five common parameters 1 of the FDM process and determined that the shrinkage phenomena is most influential. This has been confirmed by Lanzotti et al [13] in their study of the RepRap open-source 3D printer, which revealed that layer thickness and the consequent shrinkage was the leading factor in attaining geometrically accurate parts. It was also revealed that to optimise accuracy in all Cartesian co-ordinates generally necessitates a compromise as optimising in a single direction negatively impacts on the others.…”
Section: Related Worksupporting
confidence: 54%
“…The accuracy of the part to its digital counterpart has been analysed by Sood et al [12] who applied Taguchi's design of experiments on five common parameters 1 of the FDM process and determined that the shrinkage phenomena is most influential. This has been confirmed by Lanzotti et al [13] in their study of the RepRap open-source 3D printer, which revealed that layer thickness and the consequent shrinkage was the leading factor in attaining geometrically accurate parts. It was also revealed that to optimise accuracy in all Cartesian co-ordinates generally necessitates a compromise as optimising in a single direction negatively impacts on the others.…”
Section: Related Worksupporting
confidence: 54%
“…The nozzle which has controllable diameter and speed influences the quality of the printed part and the productivity of the process [51]. Generally, raw materials are produced in 1.75-mm and 3-mm diameter filaments, and nozzle diameters are varying from 0.1 to 1 mm [30].…”
Section: Nozzlementioning
confidence: 99%
“…Moreover, it is interesting to evaluate the benefits that can derive, for the study of 3D shapes of fragments initially not classifiable, from the use of automatic reconstruction and classification procedures [2][3][4]. The last ones can be included among the Virtual Prototyping Techniques widely spread from engineering to humanities fields [5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%